Nursing Handover: A Content Analysis of Nurses' Handwritten Notes. (July 2021) - Timmerman, Julianna; Sitzer, Verna; Eusebio, Rhea; Reavis, Karen; Marder, Lynn
The aim of this study was to describe characteristics and content of nurses' handover tools used for handover report and congruence of content shift-to-shift. Nurses use handwritten notes to record information despite recommendations for standardizing content of handover to improve patient safety. A descriptive, cross-sectional study was conducted in a non-profit hospital in Southern California where a convenience sample of 105 registered nurses voluntarily submitted their paper handover tools. Twenty-seven types of handover tools were collected. Participants customized handover tools with color, writing implement, emphasis markings, and symbols. Content analysis revealed that most handover tools contained the patient's name, birthdate, account number, room number, medical history, allergies, code status, systems review, vital signs, medications, vascular access, test results, plan of care, and tasks. Safety/risk-related information was rarely present. Handover tools were context-specific and individualized with handwritten information that was incongruent shift-to-shift. Safety/risk-related information was rare.